Changes of physicochemical, morphological, and biological properties of fucoidan from Monascus purpureus-fermented Undaria pinnatifida: Mechanisms and implications - Yuling Yang; Hong Lin; Xiaoting Fu (Food Hydrocolloids, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Co-treatment of arsenic-rich dust and iron-bearing slag by reduction smelting: Arsenic immobilization, phase transformation, and environmental stability - Fei Chai; Jianhua Wang; Yuan Zhou; Zelin Fu; Yuling Tu; Yanjie Liang; Xiaobo Min; Liyuan Chai (Process Safety and Environmental Protection, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Integrated non-targeted metabolomics, enzyme activities and morphological analysis to elucidate the mechanisms underlying the enhancement of activity and flavor of Monascus purpureus fermented Undaria pinnatifida - Yuling Yang; Hong Lin; Xiaoting Fu (Food Research International, 2026)

Warming‐Induced Carbon Vulnerability in Permafrost Forests: A Shift in Q 10 From Continuous to Discontinuous Zones - Changjiang Huang; Tadeo Sáez‐Sandino; Guiyao Zhou; Lingyan Zhou; Tongyao Kong; Yuling Fu; Hongyang Chen; Yimin Zhu; Shuying Qiu; Kui Xue; Chongwei Fan; Lei Cao; et al. (Global Change Biology, 2026)
Permafrost forests harbor vast, climate‐sensitive carbon (C) reservoirs whose vulnerability largely depends on temperature sensitivity of microbial respiration ( Q 10 ). However, substantial uncertainties persist in predicting Q 10 patterns due to complex interactions among multiple ecological factors. Here, we conducted a standardized field survey with controlled incubations across a regional gradient from continuous permafrost (CP) and discontinuous permafrost (Dis‐CP, including sporadic and isolated ones) in the Greater Khingan Mountains to quantify Q 10 values and identify their main ecological controls. We found that the Q 10 values were significantly higher in CP than Dis‐CP forests, indicating a stronger microbial respiratory response to warming in the coldest permafrost regions. Statistical analysis revealed that the soil microbiome was the most important factor explaining Q 10 values in CP forest (47.8%), whereas a distinct set of factors (plant production, fine texture, substrate quality, and mean annual ground temperature) explained the largest proportion (63.2%) of Q 10 variation in Dis‐CP forests. Our findings suggest that warming‐induced permafrost degradation is likely to shift the dominant controls for Q 10 from microbial community to abiotic and plant‐related factors, while enhancing greenhouse gas emissions from permafrost soils.

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Non-linear and temporally dynamic effects of built environment and trip attributes on metro competitiveness - Yuqing Zhou; Xiao Fu; Yuling Xie; Tianli Tang; Guonian Lü (Journal of Transport Geography, 2025)

Fermentation of Pyropia spp. seaweed: a comprehensive review on processing conditions, biological activities and potential applications in the food industry - Yuling Yang; Hong Lin; Xiaoting Fu (Critical Reviews in Food Science and Nutrition, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Microbial Life History Mediates the Drought‐Induced Decrease in Wood Decomposition in Subtropical Forests - Shuxian Jia; Xuhui Zhou; Yuling Fu; Guiyao Zhou; Lingyan Zhou; Xinxin Wang; Zheng Jiang; Jordi Sardans; Josep Penuelas (Ecology Letters, 2025)
Progressive intensification of drought regimes worldwide threatens wood decomposition ‐ a critical biogeochemical process in forest carbon cycling. However, the interactions between microbial strategies, wood traits and microclimate in regulating wood decomposition remain poorly understood under drought conditions. In a throughfall exclusion experiment (control 35% and 70% rainfall reduction) across 12 tree species, we found that drought‐induced reductions in wood CO 2 efflux rates were primarily driven by wood traits (density and carbon reduction) and shifts in fungal K / r ‐strategies. Coarse wood debris with higher Basidiomycota and lower Ascomycota abundance decomposed faster. Significant positive correlations were observed between fungal K / r ‐strategies and wood CO 2 efflux under control, 35%, and 70% rainfall reduction, while bacterial strategies showed no correlation. Our findings highlight the greater drought sensitivity of fungi than bacteria, emphasising their critical role in forest carbon dynamics and informing carbon models to improve the prediction of climate‐biosphere feedback in the changing world.

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Nitrogen input alleviates the priming effects of biochar addition on soil organic carbon decomposition - Xuhui Zhou; Zhiqiang Feng; Yixian Yao; Ruiqiang Liu; Junjiong Shao; Shuxian Jia; Yining Gao; Kui Xue; Hongyang Chen; Yuling Fu; Yanghui He (Soil Biology and Biochemistry, 2025)

Opposite effects of soil pH on bacteria and fungi β diversity in forests at a continental scale - Changjiang Huang; Yanghui He; Lingyan Zhou; Ruiqiang Liu; Hongyang Chen; Zhenggang Du; Yuling Fu; Yimin Zhu; Yuxuan Zhou; Chuansheng Wu; Guiyao Zhou; Xuhui Zhou (Journal of Environmental Management, 2024)

A transition from arbuscular to ectomycorrhizal forests halts soil carbon sequestration during subtropical forest rewilding - Ruiqiang Liu; Xuhui Zhou; Yanghui He; Zhenggang Du; Hongyang Chen; Yuling Fu; Liqi Guo; Guiyao Zhou; Lingyan Zhou; Jie Li; Hua Chai; Changjiang Huang; et al. (Science of The Total Environment, 2024)

Fungi and bacteria trade-off mediates drought-induced reduction in wood decomposition - Shuxian Jia; Tengfeng Yuan; Yuling Fu; Josep Penuelas; Guiyao Zhou; Lingyan Zhou; Dingqin Liu; Yanghui He; Ruiqiang Liu; Xinxin Wang; Bingqian Song; Zheng Jiang; et al. (CATENA, 2024)

Drought- induced decrease in tree productivity mainly mediated by the maximum growth rate and growing-season length in a subtropical forest - Zheqi Zhang; Lingyan Zhou; Chunyan Lu; Yuling Fu; Zhizhuang Gu; Yang Chen; Guodong Zhang; Xuhui Zhou (Forest Ecology and Management, 2024)

A methodological review of compound-specific radiocarbon analysis for polycyclic aromatic hydrocarbons in environmental matrices - Yu Fu; Rui Zhang; Shaopeng Rong; Yuling Wu; Ying Wu; Miaolei Ya (Environmental Pollution, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Evolved Late Mesozoic continental arc: Constraints of detrital zircons from the western East China Sea - Yuling Deng; Changhai Xu; Shunli Gao; Qiang Fu; Yuanyuan Li (International Geology Review, 2024)

Lithologic control of priming effect in subtropical forest - Tiangang Tang; Qi Zhang; Ruitong Fu; Pengpeng Duan; Yuling Zhang; Xinyi Yang; Kelin Wang; Dejun Li (CATENA, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Persulfate oxidation of norfloxacin by cobalt doped water hyacinth biochar composite: The key role of cobalt and singlet oxygen - Yunqiang Yi; Yue Fu; Yu Wang; Yuling Cai; Yifeng Liu; Zhimin Xu; Zenghui Diao (Journal of Water Process Engineering, 2024)

Drought-induced changes in rare microbial community promoted contribution of microbial necromass C to SOC in a subtropical forest - Xinxin Wang; Lingyan Zhou; Yuling Fu; Zheng Jiang; Shuxian Jia; Bingqian Song; Dingqin Liu; Xuhui Zhou (Soil Biology and Biochemistry, 2024)

Distinctive interphasial properties and high structural reversibility endowed by B-/CN– electrolyte additive and its superior electrochemical performance for graphite/LiCoO2 pouch cells - Shuai Chen; Xinyang Wen; Yili Chen; Zhiyong Xia; Qiurong Chen; Lingling Huang; Haonan Huang; Haowen Pan; Yuling Fu; Jiarong He; Weishan Li (Chemical Engineering Journal, 2024)

Co-application of biochar and organic amendments on soil greenhouse gas emissions: A meta-analysis - Jia Fu; Xuhui Zhou; Yanghui He; Ruiqiang Liu; Yixian Yao; Guiyao Zhou; Hongyang Chen; Lingyan Zhou; Yuling Fu; Shahla Hosseini Bai (Science of The Total Environment, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

Face it and shoulder it jointly: from personal experience to mitigation behavior of climate change - Yuling Fu; Jiaxin Shi; Dan Su; Fumin Deng (Environment, Development and Sustainability, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Projecting extreme climate events in China’s Loess Plateau: multiple RCMs and emission scenarios corrected by a trend-preserving method - Yuling Ren; Jingpeng Zhang; Bingbing Li; Jinxia Fu; Zhi Li (Theoretical and Applied Climatology, 2023)

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

Grazing and global change factors differentially affect biodiversity‐ecosystem functioning relationships in grassland ecosystems - Miao He; Yuhan Pan; Guiyao Zhou; Kathryn E. Barry; Yuling Fu; Xuhui Zhou (Global Change Biology, 2022)
Grazing and global change (e.g., warming, nitrogen deposition, and altered precipitation) both contribute to biodiversity loss and alter ecosystem structure and functioning. However, how grazing and global change interactively influence plant diversity and ecosystem productivity, and their relationship remains unclear at the global scale. Here, we synthesized 73 field studies to quantify the individual and/or interactive effects of grazing and global change factors on biodiversity‐productivity relationship in grasslands. Our results showed that grazing significantly reduced plant richness by 3.7% and aboveground net primary productivity (ANPP) by 29.1%, but increased belowground net primary productivity (BNPP) by 9.3%. Global change factors, however, decreased richness by 8.0% but increased ANPP and BNPP by 13.4% and 14.9%, respectively. Interestingly, the strength of the change in biodiversity in response to grazing was positively correlated with the strength of the change in BNPP. Yet, global change flipped these relationships from positive to negative even when combined with grazing. These results indicate that the impacts of global change factors are more dominant than grazing on the belowground biodiversity‐productivity relationship, which is contrary to the pattern of aboveground one. Therefore, incorporating global change factors with herbivore grazing into Earth system models is necessary to accurately predict climate‐grassland carbon cycle feedbacks in the Anthropocene.

MiR-221-3p regulates the microvascular dysfunction in diabetic retinopathy by targeting TIMP3 - Chongxian Wang; Yuling Lin; Yanqin Fu; Dongming Zhang; Yaping Xin (Pflügers Archiv - European Journal of Physiology, 2020)

AG1031 induces apoptosis through suppressing SIRT1/p53 pathway in human neuroblastoma cells - Jingxuan Fu; Hui Zhang; Yuling Zhang; Tao Zhang (Molecular and Cellular Biochemistry, 2019)

Differential magnitude of rhizosphere effects on soil aggregation at three stages of subtropical secondary forest successions - Ruiqiang Liu; Xuhui Zhou; Jiawei Wang; Junjiong Shao; Yuling Fu; Chao Liang; Enrong Yan; Xiaoyong Chen; Xihua Wang; Shahla Hosseini Bai (Plant and Soil, 2019)

Effects of livestock grazing on grassland carbon storage and release override impacts associated with global climate change - Guiyao Zhou; Qin Luo; Yajie Chen; Miao He; Lingyan Zhou; Douglas Frank; Yanghui He; Yuling Fu; Baocheng Zhang; Xuhui Zhou (Global Change Biology, 2019)
Predicting future carbon (C) dynamics in grassland ecosystems requires knowledge of how grazing and global climate change (e.g., warming, elevated CO 2 , increased precipitation, drought, and N fertilization) interact to influence C storage and release. Here, we synthesized data from 223 grassland studies to quantify the individual and interactive effects of herbivores and climate change on ecosystem C pools and soil respiration (Rs). Our results showed that grazing overrode global climate change factors in regulating grassland C storage and release (i.e., Rs). Specifically, grazing significantly decreased aboveground plant C pool (APCP), belowground plant C pool (BPCP), soil C pool (SCP), and Rs by 19.1%, 6.4%, 3.1%, and 4.6%, respectively, while overall effects of all global climate change factors increased APCP, BPCP, and Rs by 6.5%, 15.3%, and 3.4% but had no significant effect on SCP. However, the combined effects of grazing with global climate change factors also significantly decreased APCP, SCP, and Rs by 4.0%, 4.7%, and 2.7%, respectively but had no effect on BPCP. Most of the interactions between grazing and global climate change factors on APCP, BPCP, SCP, and Rs were additive instead of synergistic or antagonistic. Our findings highlight the dominant effects of grazing on C storage and Rs when compared with the suite of global climate change factors. Therefore, incorporating the dominant effect of herbivore grazing into Earth System Models is necessary to accurately predict climate–grassland feedbacks in the Anthropocene.

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling - Qianfeng Fu; Yuling Jiang; Daxin Zhang; Xiuli Liu; Junfeng Guo; Jinlong Zhao (Molecular and Cellular Biochemistry, 2016)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

QTL identification of grain protein concentration and its genetic correlation with starch concentration and grain weight using two populations in maize (Zea mays L.) - Yuling Li; Yanzhao Wang; Mengguan Wei; Xuehui Li; Jiafeng Fu (Journal of Genetics, 2009)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.